Immersive Stories: From Technological Determinism Towards Narrative Determinism - Jorge Vázquez-Herrero (Media and Communication)
Following the wave of immersive production that occurred between 2015 and 2018, and in the face of new virtual, augmented, and mixed-reality devices, this article discusses the need to move from a technology- or device-focused perspective in the analysis and use of immersive technology towards a story-focused or story-first perspective. It starts with a technological perspective, contextualising the evolution of immersive technologies and their interpretation from a technological determinism point of view. Secondly, the ecological perspective provides an integrative reading of the technique, its use, and its experience, based on the concept of the environment. Finally, and after acknowledging previous research on the effects of immersive media on the audience, the article considers the narrative elements that are reinforced by immersive technologies in journalism and nonfiction, based on the qualitative analysis of projects. The article highlights narrative resources associated with the social character of the story, the spatio-temporal framework, and the emotional impact. It suggests a shift towards “narrative determinism,” which would allow us to analyse and employ immersive resources in terms of their contribution to storytelling and to overcome the limitations of perspectives that are highly dependent on specific platforms or technologies.